Skylight Light Intensity Data Logging System - A. Udina; Lc Jain (Active and Passive Electronic Components)
The design of a skylight intensity data logging system is presented. The proposed system is able to accept 32 inputs in two 16 input blocks with capabilities for further expansion. A typical application would be to simultaneously monitor real time change in light intensity in two skylight units, over a chosen periods of minutes, hours or days.